2018
DOI: 10.1111/bcp.13788
|View full text |Cite
|
Sign up to set email alerts
|

Significantly lower CYP2D6 metabolism measured as the O/N‐desmethylvenlafaxine metabolic ratio in carriers of CYP2D6*41 versus CYP2D6*9 or CYP2D6*10: a study on therapeutic drug monitoring data from 1003 genotyped Scandinavian patients

Abstract: Aims CYP2D6*9, CYP2D6*10 and CYP2D6*41 are the most frequent reduced‐function CYP2D6 alleles in Caucasians. Despite lacking in vivo evidence, they are collectively classified with an enzyme activity score of 0.5. Thus, the aim of this study was to compare the functional impact of CYP2D6*9, CYP2D6*10 and CYP2D6*41 on CYP2D6 metabolism in a large patient population. Methods A total of 1003 patients (mainly Caucasians) with data on CYP2D6 genotype and serum concentrations of venlafaxine and metabolites were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 30 publications
(59 reference statements)
7
31
0
Order By: Relevance
“…This is supported by recent findings from Haslemo et al 22 who found that carriers of CYP2D6*41 had a significantly lower CYP2D6-mediated metabolism of venlafaxine compared with a pooled group of CYP2D6*9−10 carriers. Based on the metabolic ratio of O/N-desmethylvenlafaxine, they estimated an activity score of 0.095 for CYP2D6*41 and 0.34 for CYP2D6*9-10.…”
Section: Articlesupporting
confidence: 84%
“…This is supported by recent findings from Haslemo et al 22 who found that carriers of CYP2D6*41 had a significantly lower CYP2D6-mediated metabolism of venlafaxine compared with a pooled group of CYP2D6*9−10 carriers. Based on the metabolic ratio of O/N-desmethylvenlafaxine, they estimated an activity score of 0.095 for CYP2D6*41 and 0.34 for CYP2D6*9-10.…”
Section: Articlesupporting
confidence: 84%
“…Interestingly, a recent study based on >1000 Norwegian samples from routine therapeutic drug monitoring of the antidepressant venlafaxine arrived at a similar conclusion regarding a surprisingly great impact of the CYP2D6*41 allele on the individual metabolic capacity. 14 It follows that the group of poor bioactivators of tamoxifen in clinical practice might be substantially larger than now understood from the definition of PM, which is currently restricted to carriers of 2 null alleles. In several studies, such PM patients have been associated with a worse prognosis than other genotypes during adjuvant treatment with tamoxifen 6-9,29 but perhaps the conservative PM definition will fail to detect that additional CYP2D6 genotypes with very low metabolic activity also could be at high risk of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…The overall idea would be to use this patient stratification for individualized dose recommendations based on CYP2D6 genotype. However, intermediate metabolizers include a wide range of different allele combinations that clearly differ in their corresponding impact on the individual CYP2D6 metabolic activity, 13–17 and, for some variant alleles, this might even be explained by substrate‐dependent alterations in metabolic activity 18 . It follows that the conventional approach to ascribe all reduced‐function CYP2D6 alleles an anticipated 50% reduction of metabolic capacity compared to normal/fully functional alleles, is indeed simplistic and should be open for corrections over time 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the metabolism of venlafaxine in the primary metabolic pathway to O-desmethylvenlafaxine to N-desmethylvenlafaxine in the secondary metabolic pathway in the CYP2D6 isoform was used to identify variant alleles. The metabolic ratio varied from 0.47 for the Null/Null genotype to 68.18 for the *1/*4XN or *1/*41Xn ultrarapid metabolisers, demonstrating the importance of identifying the patients' genomics to be aware of the wide ranges of metabolism [80].…”
Section: Genotype Functionalmentioning
confidence: 99%